EfektifitasEmulsi Lilin Lebah Sebagai Bahan Pelapis Buah Jeruk Siam (Citrus nobilis Lour var. microcarpa) terhadap Mutu Selama Penyimpanan - Made Nanda Saputra; I Made Supartha Utama; Ni Luh Yulianti (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2019)
The purposes of this research was to determine the effects of various concentrations of beeswax emulsion as a coating material on the quality of Siam citrus fruits during storage. The research used completely randomized design (CRD) with three different concentration of beeswax emulsion in water consisted of 0%, 2%, and 4%. Fruit without treatment provided as a control. The analysis of variance showed that the emulsion concentrations of significantly (P<0.05) affected the weight loss, damage intensity, total soluble solid, texture,color difference, vitamin C, total acid and organoleptic prefrences (peel color, texture, flavor, and overall acceptance) of the fruits. The concentration of 4% was the best beeswax emulsion to delay quality deterioration of citrus fruits during storage at the room temperature.